Reevaluating the Pursuit of Defense Investment. (November 2014) - Doussard, Marc
In 2015, the Pentagon will likely announce a round of military base closures and expansions with the power to remake regional economies throughout the United States. Current estimates of the impact of base realignments implicitly assume that military bases have similar economic impacts. But the military is a diverse institution engaged in thousands of distinct activities, each with their own benefits to local economies. Using detailed soldier, civilian, and contracting data from two army bases, this article compares the economic impact of the main activities in which military bases engage. Because military bases source their inputs from national defense procurement networks, the economic benefits of soldier-based activities are smaller than most economic development alternatives. This finding suggests that regions facing defense contracting cuts are significantly more economically vulnerable than regions facing base closures.